A new Olmeca (Poaceae: Bambusoideae: Bambuseae) species endemic to Veracruz, Mexico - Ruiz-Sanchez, Eduardo; Marinero-Sobal, Esteban José (Phytotaxa, 2025)
Olmeca, with five described species, is one of six genera in the subtribe Guaduinae. Three Olmeca species inhabit montane cloud forests, while the other two are found in tropical rainforests. Most Olmeca species produce a typical (basic) caryopsis, but O. recta and O. reflexa form bacoid (fleshy) caryopses. Morphologically, all described Olmeca species develop one branch per node. In this study, we describe a new Olmeca species, characterized by having three to four branches per node and an unique combination of morphological traits. We provide a detailed description of this new species, along with a distribution map, photographs, and a morphological key to the species of Olmeca. With the description of this new Olmeca species, the genus now comprises six species, five of them endemic to Mexico, and contributes to Mexico’s remarkable woody bamboo diversity with a total of 61 woody bamboo species, 44 of them endemic.